Balanced Scorecard: Strategi Menuju World Class University - Qoyyimun Nafal; Prim Masrokan Mutohar; Agus Eko Sujianto (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2024)
Globalization has changed higher education institutions to improve quality and competitiveness towards becoming a world class university (WCU). Therefore, the research objective is to determine WCU using the balanced scorecard (BSC) approach with 5 (five) perspectives). The research design is a qualitative approach. This research is a case study research, namely Darussalam Gontor University (UNIDA Gontor). Data analysis is inductive, with exploratory descriptive analysis techniques. The research results show that in order to move towards WCU from the perspective of (1) organizational changes: research, it is necessary to increase international collaborative research and international publications, (2) human resource policies, it is necessary to increase the number of lecturers with professor and doctoral degrees. (3) academic programs, need to be pioneered by internationally accredited study programs, (4) Internal Governance, UNIDA Gontor has established itself as a millennial Islamic boarding school campus and is designated as a campus that implements the best integrity zone at PTKI and (5) Financial, UNIDA Gontor needs to develop and explore resources -funding sources from domestic and foreign partners to strengthen internationalization programs towards WCU.